Long-Term Vestibular Outcomes in Cochlear Implant Recipients - Rasmussen, Kasper Møller Boje; West, Niels; Tian, Luchen; Cayé-Thomasen, Per (Frontiers in Neurology, 2021)
Background: Vestibular dysfunction is likely the most common complication to cochlear implantation (CI) and may in rare cases result in persistent severe vertigo. Literature on long-term vestibular outcomes is scarce. Objective: This paper aims to evaluate vestibular dysfunction before and after cochlear implantation the long-term vestibular outcomes and follows up on previous findings of 35 consecutive adult cochlear implantations evaluated by a battery of vestibular tests. Methods: Prospective observational longitudinal cohort study of 35 CI recipients implanted between 2018 and 2019, last follow-up was conducted in 2021. All patients were vestibular evaluated at the CI work-up (T0) and at two postoperative follow-ups (T1 and T2), 4 and 14 months after implantation, respectively. Results: VHIT testing showed 3/35 ears had abnormal VHIT gain preoperatively which increased insignificantly to 4/35 at the last follow-up (p = 0.651). The mean gain in implanted ears decreased insignificantly from 0.93 to 0.89 (p = 0.164) from T0 to T2. Preoperatively, 3 CI ears had correction saccades which increased to 11 at T2 (p = 0.017). Mean unilateral weakness increased from 19% to 40 from T0 to T2 (p < 0.005), and the total number of patients with either hypofunctioning or areflexic semi-circular canals increased significantly from 7 to 17 (p < 0.005). 29% of CI ears showed cVEMP responses at T0, which decreased to 14% (p = 0.148) at T2. DHI total mean scores increased slightly from 10.9 to 12.8 from T0 to T1, remained at 13.0 at T2 (p = 0.368). DHI scores worsened in 6/27 patients and improved in 4/27 subjects from T0 to T2. Conclusion: This study reports significant deterioration in vestibular function 14 months after cochlear implantation, in a wide range of vestibular tests. VHIT, caloric irrigation and cVEMP all measured an overall worsening of vestibular function at short term postoperative follow-up. No significant deterioration or improvement was measured at the last postoperative follow-up, thus vestibular outcomes reached a plateau. Despite vestibular dysfunction, most of the patients report less or unchanged vestibular symptoms.